Natural gallic acid catalyzed aerobic oxidative coupling with the assistance of MnCO3 for synthesis of disulfanes in water. Issue 6 (20th February 2019) - Song, Lijuan; Li, Wenhao; Duan, Wenxue; An, Jichao; Tang, Shanyu; Li, Longjia; Yang, Guanyu
Abstract : Renewable low-toxic gallic acid serves as an efficient organocatalyst in assistance of MnCO3 for aerobic oxidative coupling of thiols to symmetrical and/or unsymmetrical disulfanes in water. Abstract : The formation of S–S bonds has great significance and value in synthetic chemistry and bioscience. To pursue a sustainable approach for such a synthesis, an aerobic oxidative coupling method for the efficient preparation of organic disulfanes, using a low-toxic natural gallic acid as an organocatalyst, inexpensive MnCO3 as a cocatalyst, O2 as the terminal oxidant and water as the solvent, has been successfully developed. Such metal–organic cooperative catalytic protocol provided an access to various symmetrical and unsymmetrical disulfanes in up to 99% yield. Gram scale synthesis with practical convenience and low loading of catalysts further illustrates the practicability of our method.